Real-time velocity regulation for productivity optimization in laser cutting. Issue 1 (2021) - Pacher, Matteo; Strada, Silvia; Tanelli, Mara; Previtali, Barbara; Savaresi, Sergio M.
Abstract: Laser cutting is an advanced industrial process, which has become the leading manufacturing technology for metal sheet processing, as it offers high flexibility and good productivity levels compared with other competing technologies. When the metal cutting process is performed in open-loop, though, to ensure that the desired quality levels are met, the cut is generally not performed at the maximum possible cutting speed and consequently its throughput is not the highest. To optimize productivity, two steps must be undertaken: first of all a reliable estimate of current cutting quality must be available online and, secondly, a closed-loop controller should regulate the cutting speed so that the desired quality is achieved. This work presents the design and the experimental validation of the full estimation and control architecture needed to regulate the cutting quality in terms of dross attachment, which is the main defect in this type of manufacturing process.